The golden door - Rodda, Emily (New York, NY : Scholastic Inc., 2013)
At night the skimmers fly over the Wall looking for human prey and the people of Weld huddle in their houses, but after his two brothers set out through the magic doors in an attempt to find the Enemy and do not come back, young Rye knows that he must follow and find them.
Originally published: Parkside, S. Aust. : Omnibus Books, c2011.
Booklist
Publisher's Weekly
School Library Journal
Booklist, December 2012
Choice, April 2013
Keywords: Brothers -- Juvenile fiction; Magic -- Juvenile fiction; Monsters -- Juvenile fiction; Adventure and adventurers -- Fiction; Brothers -- Fiction; Magic -- Fiction; Monsters -- Fiction; Adventure fiction; Brothers -- Fiction; Magic -- Fiction; Monsters -- Fiction; Adventure fiction